Reliability and validity of the Chinese version of the Walsh Family Resilience Questionnaire among community-dwelling disabled elderly individuals (WFRQ-CE) - Zhang, Xiangchun; Wang, Anni; Guan, Tingyu; Kuang, Yi; Zhang, Yuyi; Wu, Fangqi (Frontiers in Psychology, 2023)
Objective To test the reliability and validity of the Chinese version of the Walsh Family Resilience Questionnaire among community-dwelling disabled elderly individuals (WFRQ-CE). Methods Convenience sampling was used to select 566 dyads of disabled elderly individuals and their caregivers. The Walsh Family Resilience Questionnaire Chinese Version (WFRQ-C) was tested among elderly individuals. The Family Care Capacity Scale for Elderly Patients (FCCSE) was used as a concurrent validation tool for the caregivers, and the Psychological Resilience Scale (CD-RISC-10), and the Social Support Assessment (SSRS-10) were used as concurrent validation tools for both the elderly individuals and the caregivers. Results Exploratory factor analysis (EFA) revealed four common factors–“Family belief,” “Organization and problem solving,” “Family communication,” and “Utilization of external resources”–with a cumulative variance contribution rate of 56.94%. Confirmatory factor analysis (CFA) yielded the following fit indices: chi-square/freedom degree (χ2/df) = 2.007, Tucker Lewis index (TLI) = 0.900, incremental fit index (IFI) = 0.917, comparative fit index (CFI) = 0.916, parsimony goodness-of-fit index (PGFI) = 0.681, and root-mean-square error of approximation (RMSEA) = 0.060. The concurrent scales were significantly correlated with the WFRQ-C total score and the scores for each factor (r values between 0.23 and 0.60, P < 0.01). The Cronbach’s alpha coefficient was 0.93 for the WFRQ-CE and 0.87, 0.83, 0.89, and 0.65 for the four factors; the retest reliability was 0.96 for the total scale and 0.95, 0.92, 0.92, and 0.95 for the four factors; the split-half reliability was 0.85 for the total scale, and 0.81, 0.78, 0.79, and 0.68 for the four factors. Conclusion The WFRQ-CE has good reliability and validity among community-dwelling disabled elderly individuals and can be used to evaluate the level of family resilience.